The Promise of a More Abundant Life: Consumer society and the rise of the managerial state - Liverant, Bettina (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2008)
AbstractIn the decades following the turn of the century, the rising cost of living was a subject of controversy in Canada and throughout the industrialized world. No other topic, observers often noted, commanded more attention. Rising prices exacerbated wage disputes, and intensified tensions between traditional producer values and the acceptance of new patterns of purchasing. This article explores the bond formed between Canadian consumers and the managerial state by the investigation of changes in the cost of living. In order to measure changes in the prices of goods and services, it is necessary to examine the consumption practices of Canadians. This process of data collection and collation helped to normalize new consumer behaviours, and embedded the category of the Canadian citizen as a wage spender, as well as a wage earner, in the workings of government. By engaging with consumption, that is by representing, by measuring, and by categorizing the changing purchasing practices of its citizens, the state expanded its mandate and helped to shape the way Canadians came to see themselves as consumers.